Adsorption performance of 5A molecular sieve zeolite in water vaporâbinary gas environment: Experimental and modeling evaluation - AbdulKareem, F.A.; Mohd. Shariff, A.; Ullah, S.; See, T.L.; Keong, L.K.; Mellon, N. (Korean Society of Industrial Engineering Chemistry, 2018)
In this work GERG2008 EoS was incorporated in a volumetric-gravimetric-chromatographic technique. The system utilized to measure in-mixtures components experimental selective isotherms individually, with the ability to analyze water vaporâgas components in the same mixture. 5A zeolite was used as a solid adsorbent for binary and ternary CO2/CH4/H2O mixtures adsorption at 50 Â°C and 70 Â°C temperature up to 10 bar pressure. Artificial neural network (ANN) modeling was applied to predict ternary and binary gaseous with the presence of water mixtures. This study delivered better clarification in the field of selectivity and reliability in the term of multicomponent and dual phase mixtures analysis. Â© 2018 The Korean Society of Industrial and Engineering Chemistry